Sexual Crime Cases Those Reflected Penalty Courts in Samsun - Aydın, Berna; Çolak, Başar (The Bulletin of Legal Medicine, 2004)
In this study, to determine the characteristic features of sexual crime cases and to evaluate the existing differences related to sexual crime cases in the base of changes made in Turkish Penalty Law were aimed. All decisions belong to lawsuit files those were arrived a decision in Samsun 1st Penalty Courts between the years 1999-2003 were examined and lawsuits about sexual crime cases were included in the study. While all the accuseds were found out as males, only 9,4% of victims were males. Those were found out that the most of accuseds (43,4%) were in the groups of 21-30 years while the most of the victims (31,6%) were in 16-18 years. The most frequently sexual crimes reflected to law court were determined as to violate crimes. All of the individuals belonging to medicine or law, who’s interested with medical and judicial aspect of sexual crimes, must be informed about characteristic features of sexual crimes beside new legislation. Sexual crimes evaluation centres must be organized in every cities and big countries.Key words: Sexual crime, sexual assault, accused, victim, court decisions.
Keywords: sexual crime; sexual assault; accused; victim; court decisions